Analysis of Land Management Achievement Activities in the Reclamation Stage at PT. XYZ - I Putu Putrawiyanta; Neny Fidayanti; Noveriady Noveriady; Novalisae Novalisae (Universitas Islam Raden Rahmat, Malang, 2026)
Land reclamation is a crucial effort to restore former mining land so that it can function ecologically and economically again. XYZ conducts reclamation activities to meet applicable regulatory standards, therefore an internal assessment is required first before reporting to the ministry. This study aims to analyze the achievements of land management activities at the reclamation stage in PT. XYZ. The research method used is quantitative descriptive, with data collected through field observation and document analysis. The results of the study show that PT. XYZ has reached 25% of the reclamation plan in the first phase, with land management activities running for ±2 months. However, this study also identified obstacles such as less fertile soil conditions and high rainfall, as well as the absence of erosion and water control buildings made by the company, even though they are included in the reclamation activity plan. One of the settlement options that need to be done to achieve optimal reclamation success is to increase tools and working hours at the reclamation activity site, considering that the success of reclamation is the basis for company reporting and the ministry's assessment of the sustainability of the company's activities.